Ethical Foundations of Family Communication in Sayyidina Ali ibn Abi Talib’s Thought - Baiq Citra Handayani; Muhammad Ahyar; Wardi Sahri; Lalu Agus Murzaki; Abdussyakur Abdussyakur (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
Family communication plays a decisive role in shaping moral integrity, emotional stability, and ethical continuity within human relationships. This study examines how Sayyidina Ali ibn Abi Talib conceptualizes ethical communication and how his teachings can strengthen family communication within a normative religious framework. Employing a qualitative normative–religious research design, the study conducts an interpretative library-based analysis of Nahj al-Balaghah as the primary source, supported by classical and contemporary Islamic ethical scholarship. The findings identify five interrelated ethical principles governing family communication: wisdom (hikmah), truthfulness (sidq), gentleness (rifq), self-restraint (hilm), and moral accountability in speech. These principles demonstrate that communication is not a neutral social skill but a morally accountable practice that reflects character and spiritual consciousness. The study contributes a coherent normative ethical framework that integrates classical Islamic moral philosophy into contemporary discourse on family communication. It implies that strengthening family relationships requires ethical reflection, emotional discipline, and moral responsibility in everyday speech.